2016
DOI: 10.1002/jls.21427
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Presence as a Key Factor Toward Sustainability Leadership

Abstract: In the current article, we describe how individual experiences of presence may be a key factor in giving birth to the kind of leadership that enables deep sustainability. The empirical data come from two studies of the same theme: (a) an international action research project about Waking Up Moments at Work and (b) a Finnish phenomenographical study about experiences of presence. Both studies address the generative qualities of waking up or presence, suggest the value of such experiences as catalysts for inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Evidence from environmental psychological research indeed confirmed that being in nature has various psychological effects, some of which resonate closely with the components of authentic leadership. These effects include stress reduction (Bratman, Hamilton, & Daily, ; Kaplan, ; Ulrich et al, ); attention restoration (Berman, Jonides, & Kaplan, ; Cole & Hall, ); emotional well‐being (Hinds, ; Hinds & Sparks, ; Zelenski & Nisbet, ); personal development and increased self‐awareness (D'Amato & Krasny, ; Friese, Pittman, & Hendee, ; Heintzman, ; Talbot & Kaplan, ); an increase in creativity, inspiration and spirituality, greater authenticity, and connectedness (Frederickson & Anderson, ; Howell, Dopko, Passmore, & Buro, ; Kaye, ); and potential for contributing to sustainability (Koskela & Goldman Schuyler, ). Thus, immersion in wilderness could induce high‐impact experiences, which might act as trigger events fostering intrapersonal change (Boniface, ; Maslow, ; McDonald, Wearing, & Ponting, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence from environmental psychological research indeed confirmed that being in nature has various psychological effects, some of which resonate closely with the components of authentic leadership. These effects include stress reduction (Bratman, Hamilton, & Daily, ; Kaplan, ; Ulrich et al, ); attention restoration (Berman, Jonides, & Kaplan, ; Cole & Hall, ); emotional well‐being (Hinds, ; Hinds & Sparks, ; Zelenski & Nisbet, ); personal development and increased self‐awareness (D'Amato & Krasny, ; Friese, Pittman, & Hendee, ; Heintzman, ; Talbot & Kaplan, ); an increase in creativity, inspiration and spirituality, greater authenticity, and connectedness (Frederickson & Anderson, ; Howell, Dopko, Passmore, & Buro, ; Kaye, ); and potential for contributing to sustainability (Koskela & Goldman Schuyler, ). Thus, immersion in wilderness could induce high‐impact experiences, which might act as trigger events fostering intrapersonal change (Boniface, ; Maslow, ; McDonald, Wearing, & Ponting, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…World economist Brian Arthur has said: "Every profound innovation is based on an inward bound journey; ongoing to a deeper place where knowing comes to the surface" (Senge, Scharmer, Jaworski, and Flowers, 2005, p.13). Consequently, solving global crises requires new kinds of creativity and more sustainable innovativeness instead of old paradigms and patterns (Koskela and Goldman Schuyler, 2016;Moss, 2012;Scharmer, 2009;Scharmer, 2010;Scharmer and Kaufer, 2013;Sveiby and Skuthorpe, 2006). We will not be able to solve our problems if we disregard the global problems facing our planet and if we do not reconsider our approach consciously towards the fundamentals that uphold life, the unity of all living in the planet.…”
Section: The Need Of a More Holistic Point Of Viewmentioning
confidence: 99%
“…It is necessary to change a reductive kind of awareness that is based on alienation and separation to one of co-creation (Senge et al, 2005). This is a new point of view to the Western technological thinking, which has its roots in Judeo-Christian traditions, where nature is considered to be separated from human beings, and instead it exists for the benefit of humanity (Klemola, 2004;Koskela and Goldman Schuyler, 2016;Singer, 1993;Varto and Veenkivi, 1997;Varto, 2011). In many indigenous cultures, nature has been the critical factor for the production function (Kaipa, 2007;Scharmer and Kaufer, 2013;Sveiby and Skuthorpe, 2006;Sveiby, 2011;Varto and Veenkivi, 1997).…”
Section: The Need Of a More Holistic Point Of Viewmentioning
confidence: 99%
See 2 more Smart Citations